1984
DOI: 10.1002/bit.260261203
|View full text |Cite
|
Sign up to set email alerts
|

Cellular reporoduction and extracellular polymer formation by Pseudomonas aeruginosa in continuous culture

Abstract: The kinetics of cellular reproduction and the rate and extent of synthesis of extracellular polymeric substances (EPS) were investigated for P. aeruginosa growing in glucose-limited chemostats. mu(max) and K(s) estimates of 0.4 h(-1) and 2 mg glucose C/L, respectively, at 25 degrees C were obtained for this bacterium. The extent of EPS formation was inversely related to the growth rate of P. aeruginosa. The rate of EPS formation had both growth- and non-growth-associated components. The growth-associated polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 22 publications
6
40
1
1
Order By: Relevance
“…However, previous experiments have shown that faster-growing biofilms are more susceptible to flow-induced detachment (62)(63)(64)(65). This dependency may occur because fastgrowing genotypes invest less in secretions of exopolymeric substances that glue cells together (63) or because rapidly growing genotypes form biofilms with more fragile morphologies, rendering them more susceptible to detachment (55,66). To model how covariance between growth and detachment influences bacterial competition, we extended our model using the parameterization of Speitel and DiGiano (62), who empirically quantified this coupling in porous environments using radiolabeled carbon sources.…”
Section: Accounting For Potential Covariance Between Rates Of Bacterimentioning
confidence: 99%
“…However, previous experiments have shown that faster-growing biofilms are more susceptible to flow-induced detachment (62)(63)(64)(65). This dependency may occur because fastgrowing genotypes invest less in secretions of exopolymeric substances that glue cells together (63) or because rapidly growing genotypes form biofilms with more fragile morphologies, rendering them more susceptible to detachment (55,66). To model how covariance between growth and detachment influences bacterial competition, we extended our model using the parameterization of Speitel and DiGiano (62), who empirically quantified this coupling in porous environments using radiolabeled carbon sources.…”
Section: Accounting For Potential Covariance Between Rates Of Bacterimentioning
confidence: 99%
“…They may produce extracellular polymers (Characklis, 1973(Characklis, , 1981Characklis and Cooksey, 1983;Daniels, 1980;Robinson et al, 1984) which are usually lumped together with cells in dry biomass measurements, resulting in overestimation of the activity of immobilized biomass. In addition, cell location in the biofilm can affect its quality and activity, since profiles of environmental conditions such as substrate concentration often exist.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of polymer observed decreased as Oc increased, indicating either reduced exopolymer production, increased biodegradation of polymer, or increased adsorption of polymer onto suspended solids (32). In a pure culture of Pseudomonas aeruginosa under conditions of carbon limitation, Robinson et al observed that extracellular polymer concentration increased with decreasing dilution rates (increasing EO) despite constant or decreasing cell populations (33). However, Mian et al found that both cell concentration and polymer concentration of P. aeruginosa were independent of dilution rate under conditions of nitrogen limitation (20).…”
Section: Introductionmentioning
confidence: 99%